Dzielimy się doświadczeniemFrequency and determinants of renal dysfunction in cardiovascular patients - Rozentryt, Piotr; Nowak, Jolanta; Bronisz, Marek; Brachowska, Agnieszka; Buczek, Małgorzata; Kaszycka, Marta; Michalak, Wojciech; Poloński, Lech (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2007)
Background: Chronic impairment of kidney function is a strong risk factor of cardiovascular diseases and predicts most important clinical outcomes. The relationship between plasma creatinine and glomerular filtration rate (GFR) has been shown to be nonlinear; hence normal plasma creatinine may be present in a patient with significantly diminished GFR. The use of creatinine as the only marker of kidney function may result in inappropriate diagnostic (contrast) and therapeutic decisions (drugs dosage). Aim: Our aims were to assess the frequency of chronic kidney impairment in patients hospitalised in two cardiology departments and to analyse predictors for simultaneous presence of normal creatinine and reduced GFR. Material and methods: In 333 patients referred for hospitalisation in a cardiology department (mean age: 59.7 years, 66% male) we estimated GFR using the Cockroft-Gault formula and assessed the association of common cardiovascular risk factors with GFR <60 ml/min x 1.73 m 2 . Finally we performed an analysis of predictors of simultaneous presence of plasma creatinine below 1.25 mg/dl (110 µmol/l) and GFR <60 ml/min x 1.73 m 2 . Results: In 24% of patients GFR estimated using the Cockroft-Gault formula fell below 60 ml/min x 1.73 m 2 . These patients were more likely to be older, smaller, and had signs of atherosclerosis. There was only a trend for more frequent presence of diabetes, hypertension, hypercholesterolaemia, smoking and family history of cardiovascular diseases in this group. In multivariable analysis low GFR was predicted only by older age and high BMI. In 11% of all patients GFR <60 ml/min x 1.73 m 2 was accompanied by plasma creatinine <1.25 mg/dl. The independent predictors of this important laboratory situation were female gender, diabetes and smoking. Conclusions: Chronic renal impairment is present in about a quarter of patients hospitalised in cardiology departments. In one out of ten GFR <60 ml/min x 1.73 m 2 cannot be detected based on plasma creatinine. Three simple clinical features are independently associated with this dangerous clinical situation.